Efeito das escolas de tempo integral na proficiência dos alunos : o caso da rede estadual do RS - Schardong, Fernando (2023)
The implementation of full-time schools has been one of the strategies used by governments to combat the low levels of learning observed by the country's main educational indicators, such as IDEB. In 2016, the government of the State of Rio Grande do Sul promoted a policy of implementing full-time schools in elementary education with the aim of improving student learning. However, there is no consensus in the literature about the impacts generated by extending working hours on improving proficiency. Therefore, this study aims to evaluate whether this program had an impact on the learning of 9th year elementary school students in 2017 and 2019 in Portuguese and mathematics. Tests were also carried out in 2015, prior to the implementation of the program, as a way of controlling the model's adherence. Data on the proficiency and observable characteristics of the students used in the models were extracted from SAEB microdata and the construction of the control group was based on the criteria adopted for the schools' eligibility for the state program. The method used in this work was propensity score matching. The means tests showed that after matching there was no significant difference between the means of the control group and the treatment group among the observable variables used. The results obtained from the tests carried out showed that there were no statistically significant learning gains for the Portuguese language and mathematics in the SAEB assessments carried out in 2017 and 2019. These results indicate that the objective proposed by the educational policy of the State of Rio Grande do Sul may not be achieved. It is important to highlight, however, that the benefits for students who study in full-time schools are not restricted to proficiency, but also involve other personal and family aspects not evaluated in this study